Analisa Debit Banjir Rencana DAS Rejoso Menggunakan Metode Hidrograf Satuan Sintetik Nakayasu - Arifin, Zainal; Maulidiyah, Afrikhatul (Universitas Ibn Khaldun, 2025)
Flood is an event where water overflows in a river beyond its capacity. Several areas in Indonesia, especially Pasuruan Regency, often experience flooding, one of which is the Rejoso Watershed which often experiences flooding every year. Therefore, efforts need to be made to immediately minimize the occurrence of flood disasters. By planning water structures, planned flood discharge data is needed as a basis for planning the dimensions and stability of water structures. In this study, the hydrological analysis begins by calculating the average rainfall in the area using the Thieseen polygon method, the analysis of return period rainfall using the Gumbel method which is tested using the chi-square method, then the analysis of rainfall intensity using the Mononobe method, and the hydrograph analysis using the HSS Nakaysu method. The results of the study stated that the peak discharge of the Rejoso Watershed for return periods of 2, 5, and 10 years, respectively, was 769.32 m3/sec; 971.62 m3/sec and 1116.96 m3/sec. In the period of 25, 50 and 100 years respectively, namely 1274.80 m3/sec; 1400.35 m3/sec and 1524.97 m3/sec. The planned flood discharge of the Rejoso watershed began to experience an increase in the curve at hour 0 to hour 2. While the peak discharge occurred at hour 2. At hour 3, the flood discharge of the Rejoso watershed began to experience a decrease in the curve until hour 13.